Hubungan antara persepsi tarif retribusi - Tantut Susanto, Nugroho Wiyadli Purwanta (Berita Kedokteran Masyarakat (BKM), 2006)
Background: In providing basic health services, community health center often experiences budget shortage to develop its service quality, due to budget constraint for operational activities. Decentralization gives the government chance to regulate the cost in their areas. To cover operational costs at community health centers, The Bantul District Government has set the newest tariff at community health center to improve their services quality. Objectives: This study examined correlation between perceptions on tariff and quality of services in community health center clinic of Kasihan 11 Bantul. Methods: This was a descriptive analytic non- experimental, study using cross-sectional design. The subjects were health services at the clinic, with patients as the unit of analysis, Questionnaires were distributed to 85 patients from October 1 to October 31, 2003. Result: Result shows that: (a) perception on tariff significantly affects quality services; (b) perception of tariff was well accepted for patients with influences by their education, their occupation, and their incomes; (c) the increases of perceived quality of services related to perception on tariff have been largely influenced by factors of empathy, assurance, responsiveness, reliability, and tangibles. Conclusion: Its suggested that: (a) the application of tariff be maintained and developed to increase quality of service; (b) supporting factors quality of service be prioritized for improvement; (c) the government consider financial capability of community for "swadana" economically community health services, d) providers analyze data to improve quality of service; (e) variable experiences must analyze to support perception of tariff; (f) variable customers satisfaction must analyze to improve of quality services. Keywords: perception, tariff, quality services